Feasibility of a cardiovascular cohort in a Sub-Saharan Africa community: preliminary report of the pilot project TAHES (Tanvè Health Study) in Benin. Issue 1 (1st January 2017) - Houehanou, Yessito Corine; Mizéhoun-Adissoda, Carmelle; Amidou, Salimanou; Désormais, Iléana; Houénassi, Martin; Preux, Pierre-Marie; Marin, Benoit; Houinato, Dismand; Lacroix, Philippe
ABSTRACT: Background : Faced with the growing burden of cardiovascular disease (CVD) including atherosclerotic in Sub-Saharan Africa (SSA), the development of appropriate prediction tools, based on large cohorts, appears useful for prevention. Objective : The objective of the pilot project TAHES (Tanvè Health Study) was to explore the feasibility of a large cohort study focused on CVD and risk factors in Benin. Methods : We implemented a prospective cohort over 2 years. The sample consisted of all people aged 25 years or older who had lived for at least the previous 6 months in the villages of Tanvè or Dékanmè. At baseline in February 2015, behaviours and medical histories were recorded using a standardized questionnaire adapted from the WHO Steps instrument; screening questionnaires for angina, claudication, congestive heart failure, and stroke were applied; anthropometric measures and fasting capillary blood glucose were taken. All participants were included in the follow-up phase. Surveillance of target CVD and deaths was implemented through a medical and a community network. Results : A total of 1, 195 participants were enrolled at baseline; women represented 65.5% and the median age was 39 years. The high participation rate (91.4%), the quality of baseline data, and the functionality of the events surveillance network over 8 months indicated good perspective for the feasibility of a large cohort. We recorded a 3.8% prevalence of daily smoking, 3.6% of harmful use of alcohol, 10.7% of obesity, 25.5% of high blood pressure, and 3.5% of diabetes. Prevalence of angina pectoris (2.7%), intermittent claudication (2.0%), congestive heart failure (0.9%), and stroke survival with motor impairment (3‰) were also recorded. Ten deaths occurred during the first 8 months, all within households; a cardiovascular cause was suspected in four cases. Conclusion : These preliminary results support the feasibility of establishing a cohort in Benin. It would require technical and resource support.